A Bayesian latent spatial model for mapping the cortical signature of progression to Alzheimer's disease. Issue 1 (12th February 2021) - Dai, Ning; Kang, Hakmook; Jones, Galin L.; Fiecas, Mark B.; ,
Abstract : Prior studies have shown that atrophy in vulnerable cortical regions is associated with an increased risk of progression to clinical dementia. In this work, we utilize the longitudinal structural magnetic resonance imaging (MRI) data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) to investigate the relationship between the temporally changing spatial topography of cortical thickness and conversion from mild cognitive impairment to Alzheimer's disease (AD). We develop a novel Bayesian latent spatial model that employs the spatial information underlying the thickness effects across the cortical surface. The proposed method facilitates the development of imaging markers by reliably quantifying and mapping the regional vulnerability to AD progression across the cortical surface. Simulation results showed substantial gains in statistical power and estimation performance by accounting for the spatial structure of the association. Using MRI data from ADNI, we examined the topographic patterns of anatomic regions where cortical thinning is associated with an increased risk of developing AD. Résumé : Des études précédentes ont montré que l'atrophie de régions corticales vulnérables est associée à une augmentation du risque de la progression de la démence clinique. Les auteurs utilisent les données d'imagerie par résonnance magnétique (IRM) longitudinales de l'initiative d'imagerie médicale pour la maladie d'Alzheimer (IIMMA) afin d'étudier la relation entre l'évolution dans le temps de la topographie spatiale de l'épaisseur corticale et la conversion de déficiences cognitives modérées (DCM) vers la maladie d'Alzheimer (MA). Ils développent un nouveau modèle latent spatial bayésien qui utilise l'information spatiale par rapport au cortex dans la mesure de l'effet lié à l'épaisseur corticale. La méthode proposée facilite le développement de marqueurs d'imagerie en quantifiant et en localisant de façon fiable des vulnérabilités régionales qui mènent à une progression vers la MA. Les auteurs présentent des résultats de simulations montrant des gains substantiels de puissance statistique et de performance pour l'estimation lorsque la structure spatiale de l'association est prise en compte. Avec les données d'IRM de l'IIMMA, ils examinent les motifs topographiques des régions anatomiques où l'amincissement cortical est associé à un risque accru de développer la MA.